Pengaruh Konsep Gamifikasi Dalam Model Pembelajaran IMPROVE Terhadap Kemampuan Berpikir Kritis Matematis Siswa SMP - Arini Alhaq; Rizki Wahyu Yunian Putra; Tati Apriyanti (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2023)
All students should develop their mathematical critical thinking skills to aid their learning and overcome various mathematical challenges. The purpose of this study is to find out how the idea of gamification of IMPROVE learning model affects students' mathematical critical thinking skills. This study used a quasi-experimental design to collect data by using a test in the form of description questions. Normality test and homogeneity test are the two data analysis procedures used. One-way ANOVA test was used in testing the hypothesis of this study. Based on the results of the study, the idea of gamification of IMPROVE learning model has an impact on students' mathematical critical thinking skills.